2003
DOI: 10.1109/tfuzz.2002.806315
|View full text |Cite
|
Sign up to set email alerts
|

GA-based intelligent digital redesign of fuzzy-model-based controllers

Abstract: Intelligent digital redesign involves converting a continuous-time fuzzy-model-based controller into an equivalent discrete-time counterpart for the digital control of continuous-time nonlinear systems by using the Takagi-Sugeno (TS) fuzzy models. In this paper, authors present a new global state-matching intelligent digital redesign method for nonlinear systems by using genetic algorithms (GAs). More precisely, the intelligent digital redesign problem is converted to an equivalent optimization problem, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Recent works have shown that GAs have the properties that make them a powerful technique for selecting high-performance parameters for FLCs. A simple schematic illustration of the process of GA is shown in work [1]. As shown in Fig.…”
Section: Genetic Algorithm Based Flcmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent works have shown that GAs have the properties that make them a powerful technique for selecting high-performance parameters for FLCs. A simple schematic illustration of the process of GA is shown in work [1]. As shown in Fig.…”
Section: Genetic Algorithm Based Flcmentioning
confidence: 99%
“…Wire electrical discharge machining (wire-EDM) has become a key technology for the manufacture of stamping, pressing and extrusions tools [1]. A closed-loop wire tension control system with an adaptive controller for a wire-EDM machine has been shown to keep a constant tension value as well as successfully improve the machining accuracy [2][3].…”
Section: Introductionmentioning
confidence: 99%